2022
DOI: 10.1038/s41388-022-02415-6
|View full text |Cite
|
Sign up to set email alerts
|

TRAF4 hyperactivates HER2 signaling and contributes to Trastuzumab resistance in HER2-positive breast cancer

Abstract: The HER2 receptor modulates downstream signaling by forming homodimers and heterodimers with other members of the HER family. For patients with HER2-positive breast cancer, Trastuzumab, an anti-HER2 monoclonal antibody as first-line therapy has shown significant survival benefits. However, the development of acquired resistance to Trastuzumab continues to be a significant obstacle. TNF receptor-associated factor 4 (TRAF4) upregulation was discovered to be associated with a worse clinical outcome. Here we ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…Moreover, TRAF4 is the first member of the TRAF protein family to be amplified and overexpressed in multiple human malignancies, including breast, lung, prostate and colorectal cancer, and OSCC [11][12][13]. Several lines of evidence revealed that TRAF4 was not only involved in the initiation and progression of tumors, but also in chemoresistance and radioresistance [12,[14][15][16]. Hao et al identified that TRAF4 was highly expressed in breast cancer and possessed the function of inhibiting apoptosis and promoting cancer cell proliferation via regulating the ubiquitination of spindle assembly-associated protein Eg5 [17].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, TRAF4 is the first member of the TRAF protein family to be amplified and overexpressed in multiple human malignancies, including breast, lung, prostate and colorectal cancer, and OSCC [11][12][13]. Several lines of evidence revealed that TRAF4 was not only involved in the initiation and progression of tumors, but also in chemoresistance and radioresistance [12,[14][15][16]. Hao et al identified that TRAF4 was highly expressed in breast cancer and possessed the function of inhibiting apoptosis and promoting cancer cell proliferation via regulating the ubiquitination of spindle assembly-associated protein Eg5 [17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TRAF4 activated the PI3K/AKT signaling pathway to promote the migration and invasion of hepatocellular carcinoma cells [ 26 ], and clinical evidence suggested that TRAF4 was closely associated with poor prognosis in intrahepatic cholangiocarcinoma [ 27 ]. Overexpression of TRAF4 led to trastuzumab resistance by activating HER2 signaling in HER2-positive breast cancer [ 28 ]. In glioblastoma (GBM), TRAF4 regulates caveolin 1 (CAV1) stability, and drives GBM cell stemness and temozolomide resistance by blocking ZNRF1-mediated ubiquitination and promoting USP7-mediated deubiquitination [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, it interacts with tumor necrosis factor receptor‐related factor 4 (TRAF4) and sequesters TRAF4 from activating Eg5 translation, thereby inhibiting Eg5 protein levels (Liu et al, 2018a). Moreover, studies have shown that inhibiting TRAF4 expression in breast cancer cells can reverse tamoxifen and trastuzumab resistance (Gu et al, 2022; Zhou et al, 2020). TRAF4 has been reported to be overexpressed in a variety of cancers, including breast, lung, ovarian, and others (He et al, 2022; Luo et al, 2022; Zhu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%